The Impact of Grammarly on Vocational Senior High School Students’ Writing Performance and Their Perceptions of Its Use as an Automated Writing Evaluation Tool - Ihda Wahyu Isnaini (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
After analyzing the quantitative data, the researcher grouped the students' scores from pre-test to post-test into three categories: Improved Performance, Stable Performance, and Declined Performance, using a four-level scoring rubric (Poor, Fair, Good, and Very Good). The goal of this classification is to understand how students at different proficiency levels participated in Grammarly-assisted writing. This allows identification of students who showed score increases, remained stable, or experienced decreases between the pre-test and post-test. After selecting three students from each category, the researcher conducted semi structured interviews comprising 15 questions across five categories. Based on interviews with participants, researchers identified three themes: Grammarly's Roles in Enhancing the Accuracy of Language Form, Grammarly's Impact on Writing Quality, and Limitations in Using Grammarly. They felt that Grammarly was helpful as a writing tool. Students in the declining category also had positive perceptions and felt that Grammarly was helpful. The features offered by Grammarly are also claimed to help students. By using the free version of Grammarly, students did not experience problems with limited features because they felt sufficiently assisted by the features provided in the free version. However, observations in the classroom showed that Grammarly was mostly used only during class sessions, and some students still faced technical and interpretive challenges, which limited its potential impact despite their positive perceptions. In conclusion, findings from both quantitative and qualitative data indicated that many students showed an improvement in their writing scores after using Grammarly. Additionally, the qualitative findings revealed that students' perceptions of Grammarly were generally positive. This was mainly related to the use of grammar correction, spell-checking, and punctuation features. The students believed that Grammarly could support their writing development. Grammarly can also help users become more confident when writing in English.
Reupload file repository 20 Februari 2026_Yudi
Keywords: The Impact of Grammarly; Automated Writing Evaluation Tool